Karoli IV Imperatoris Romanorum Vita Ab Eo Ipso Conscripta et Hystoria Nova De Sancto Wenceslao Martyre = Autobiography of Emperor Charles IV and His Legend of St Wenceslas (Central European medieval texts., 2001)
One of the few autobiographies to have survived from the Middle Ages, this life history of one of the most influential rulers of the fourteenth century, Charles IV of Bohemia, covers his life from birth until his election as King of Germany in 1346. Charles IV describes his childhood, spent mainly in the court of French kings, his juvenile years, his marriage and his first steps into the international political scene during the early part of the fourteenth century. A unique addition to this volume is the first ever English translation of the Legend of Saint Wenceslas, written by Charles IV of Luxemburg. This is the first autobiography to contain both the Latin narrative sources and a complete English-language translation.